(untitled) (Historia, 2021)
The article attempts to investigate the type of recreational and competitive sports which were introduced by the Messina mine management, who were British by origin, to the African communities of Messina, Harper, Campbell and Artonvilla compounds. Attention is focused on how the working class in the process of their sports activities displayed signs of conflict and division due to ethnic and regional affiliations especially in competitive sports.